Non-diffracting multi-﻿electron vortex beams balancing their electron–electron interactions - Maor Mutzafi (Nature Portfolio, 2017)
Vortex electron beams are generated using single electrons but their low beam-density is a limitation in electron microscopy. Here the authors propose a scheme for the realization of non-diffracting electron beams by shaping wavepackets of multiple electrons and including electron–electron interactions.